A review of the risks of long-term consequences associated with components of the CHOP chemotherapy regimen. (31st December 2022) - Watson, Crystal; Gadikota, Hemanth; Barlev, Arie; Beckerman, Rachel
Abstract: A common chemotherapy regimen in post-transplant lymphoproliferative disease (PTLD) following solid organ transplants (SOT) is cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP). This study reviews the quantitative evidence for long-term consequences associated with components of CHOP identified from the Children's Oncology Group Long-Term Follow-Up Guidelines. Cited references were screened using prespecified criteria (English, systematic review, randomized controlled trial n > 100, observation study n > 100, case series n > 20). Relevant data were extracted and synthesized. Of 61 studies, 66% were retrospective cohort studies, 28% were in the US, and 95% enrolled pediatric patients. No study focused specifically on the CHOP regimen. Long-term consequences for CHOP components observed in >3 studies included cardiac toxicity ( n = 14), hormone deficiencies/infertility ( n = 14), secondary leukemia ( n = 7), osteonecrosis ( n = 6), and bladder cancer ( n = 4). These effects are significant, impact a high percentage of patients, and occur as early as one year after treatment. Although none of the studies focused specifically on the CHOP regimen, 30%, 23%, and 15% evaluated alkylating agents (e.g. cyclophosphamide), anthracyclines (e.g. doxorubicin), and corticosteroids (e.g. prednisone), respectively. All three product classes had a dose-dependent risk of long-term consequences with up to 13.2-fold, 27-fold, 16-fold, 14.5-fold, and 6.2-fold increase in risk of heart failure, early menopause, secondary leukemia, bladder cancer, and osteonecrosis, respectively. Lymphoma patients had significantly elevated risks of cardiac toxicity (up to 12.2-fold), ovarian failure (up to 3.8‐fold), and osteonecrosis (up to 6.7-fold). No studies were found in PTLD or SOT. Safe and effective PTLD treatments that potentially avoid these long-term consequences are urgently needed.